Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.ejon.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Existential encounters: Nurses' descriptions of critical incidents in end-of-life cancer care

Abstract: a b s t r a c tNurses working with cancer patients in end of life care need to be prepared to encounter patients' psychosocial and spiritual distress. Aim: The aim of this study was to describe nurses' experiences of existential situations when caring for patients severely affected by cancer. Methods and sample: Nurses (registered and enrolled) from three urban in-patient hospices, an oncology clinic and a surgery clinic and a palliative homecare team were, prior to the start of a training program, invited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…On the other hand, failure to discuss a DHD may negatively impact a SPC-HP's effort to establish a relationship and consequently the ability to provide effective support, which is similar to Schwartz's findings [25]. Browall et al [24] also showed difficulties of nurses in caring for patients expressing a severe DHD. The results here showed that a possibility of overburdening due to emotional involvement [32], close relationships, or over-identification with patients exists.…”
Section: Self Protectionsupporting
confidence: 62%
“…On the other hand, failure to discuss a DHD may negatively impact a SPC-HP's effort to establish a relationship and consequently the ability to provide effective support, which is similar to Schwartz's findings [25]. Browall et al [24] also showed difficulties of nurses in caring for patients expressing a severe DHD. The results here showed that a possibility of overburdening due to emotional involvement [32], close relationships, or over-identification with patients exists.…”
Section: Self Protectionsupporting
confidence: 62%
“…Patients and caregivers often express concerns regarding psychological and physical issues, and frequently talk about causes of distress (Clayton, Reblin, Carlisle, & Ellington, 2014 (Chochinov et al, 2009). Experienced healthcare professionals are needed to meet patients' existential and spiritual needs and so they can develop self-insight regarding the finality of life (Browall, Henoch, Melin-Johansson, Strang, & Danielson, 2014 (Yun et al, 2010). Experienced healthcare professionals are needed to meet patients' existential and spiritual needs and so they can develop self-insight regarding the finality of life (Browall, Henoch, Melin-Johansson, Strang, & Danielson, 2014 (Yun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To meet patients' needs to express their existential concerns, healthcare professionals may develop a relationship of trust through effective communication skills (Johnston & Smith, 2006;Mok & Chiu, 2004). Experienced healthcare professionals are needed to meet patients' existential and spiritual needs and so they can develop self-insight regarding the finality of life (Browall, Henoch, Melin-Johansson, Strang, & Danielson, 2014). The availability of sufficient time can make it possible for healthcare professionals to better support terminally ill cancer patients, because they can use diverse methods to promote personal growth, thus helping them move towards greater existential certainty.…”
Section: Discussionmentioning
confidence: 99%
“…This is explored further in another paper by the same authors (Bailey et al, 2011a) who describe how care of the dying is seen by nurses themselves as a predominantly nursing role, implying that nurses who are 'good' at their job, and manage to develop emotional intelligence as above, find reward in their practice, leading to a more positive experience for all concerned. The idea that care of the dying is the province of nurses predominantly is borne out by other literature and could be explored further (Lopera Betancur, 2015, Browall et al, 2014, Gagnon and Duggleby, 2014, Smith, 2012.…”
Section: Staff Use Of Distancing Behavioursmentioning
confidence: 99%